2017
DOI: 10.1103/physrevb.96.085147
|View full text |Cite
|
Sign up to set email alerts
|

Magneto-optical conductivity of double Weyl semimetals

Abstract: We investigate the magneto-optical response of double Weyl semimetals whose energy dispersion is intrinsically anisotropic. We find that in the presence of a magnetic field, the most salient feature of the optical conductivity is a series of resonant peaks with the corresponding frequencies scaling linearly with the strength of the magnetic field. In addition, the optical conductivity is found to be anisotropic, with two of the three longitudinal components residing at a linear background and the remaining one… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 68 publications
3
28
0
Order By: Relevance
“…Eq. (4) is commonly found in the literature 12,17,18 where only STT influence is accounted for, while Eq. 4) and (5).…”
Section: Results and Analysismentioning
confidence: 99%
“…Eq. (4) is commonly found in the literature 12,17,18 where only STT influence is accounted for, while Eq. 4) and (5).…”
Section: Results and Analysismentioning
confidence: 99%
“…In later investigations, various modified versions of the CL are proposed [69][70][71][72][73][74][75][76][77][78][79], and also realized experimentally in atom-optical setups like photonic lattices [80,81] and cold atoms [82,83]. Intriguing topological features of the CL are reflected in the formation of AB cages [81] and the quantized Thouless pumping [84].…”
Section: The Modelmentioning
confidence: 99%
“…One version of the modified CL model concerns the case with spin-1/2 fermions and spin-orbit couplings in the ladder. Recently, such kinds of spinful CL (SCL) have been investigated in several studies [84][85][86]. It was found that the existence of spin degrees of freedom could not only modify the symmetry classification of the CL (e.g., from AIII to CII), but also induce new topological transport phenomena.…”
Section: The Modelmentioning
confidence: 99%
“…However, the BSE is computational formidable and has not yet widely applied in water. This computational burden has been greatly alleviated by the recently introduced approximate BSE solution utilizing localized basis [28][29][30]. On the other hand, the modeling of water at the molecular level is no less difficult because of the nature of the H-bond, which is a balance of many physical interactions.…”
mentioning
confidence: 99%
“…Moreover, compared to the bound exciton described by the pre-edge, the main-and post-edge contributions to the XAS spectrum are resonant excited states, which are sensitive to the intermediate-range and long-range ordering of H-bond network. Hence, a much larger simulation super cell is required to properly describe these delocalized excited states [30].…”
mentioning
confidence: 99%